Fuzzy Logic System for Menstrual Cycle Interpretation Based on BBT Data - Mohd Yazed, Muhammad Syukri; Zainodin, Ariff Farhan; Mahmud, Farhanahani (International Journal of Integrated Engineering, 2017)
Basal body temperature (BBT) data have been used for so long as a simple method in estimating the day of ovulation occurred and to understand menstrual cycle that is unique for every woman. The BBT is considered to be a reliable ovulatory index, since most women will have increased temperature in the luteal phase of the cycle. However, the problems faced are the studies of validating the efficacy using BBT and lack of research. Therefore, according to these problems, a fuzzy logic system for the predictions of ovulation occurrence, follicular and luteal phase length has been constructed to interpret the BBT data effectively and this system has been implemented on Arduino Mega 2560 microcontroller for portability purpose. As a result, according to six samples of open source BBT data obtained from the Fertility Friend website, the system enables to predict the ovulation occurrence and follicular and luteal phase length with 71.43 % of accuracy.